Brain structural trajectories in youth at familial risk for schizophrenia or bipolar disorder according to development of psychosis spectrum symptoms. (20th September 2020) - Sugranyes, Gisela; de la Serna, Elena; Ilzarbe, Daniel; Pariente, Jose Carlos; Borras, Roger; Romero, Soledad; Rosa, Mireia; Baeza, Inmaculada; Moreno, Maria Dolores; Bernardo, Miguel; Vieta, Eduard; Castro‐Fornieles, Josefina
Abstract : Background: The evaluation of child and adolescent offspring of patients with schizophrenia (SzO) or bipolar disorder (BpO) may help understand changes taking place in the brain in individuals at heightened risk for disease during a key developmental period. Methods: One hundred twenty‐eight individuals (33 SzO and 46 BpO, considered jointly as 'Familial High Risk' (FHR), and 49 controls) aged 6–17 years underwent clinical, cognitive and neuroimaging assessment at baseline, 2‐ and 4‐year follow‐up. Twenty FHR participants (11 SzO and 9 BpO) developed psychotic spectrum symptoms during follow‐up, while 59 FHR participants did not. Magnetic resonance imaging was performed on a 3Tesla scanner; cortical surface reconstruction was applied to measure cortical thickness, surface area and grey matter volume. Results: FHR participants who developed psychotic spectrum symptoms over time showed greater time‐related mean cortical thinning than those who did not and than controls. By subgroups, this effect was present in both BpO and SzO in the occipital cortex. At baseline, FHR participants who developed psychotic spectrum symptoms over time had smaller total surface area and grey matter volume than those who did not and than controls. Over time, all FHR participants showed less longitudinal decrease in surface area than controls. In those who developed psychotic spectrum symptoms over time, this effect was driven by BpO, while in those who did not, this was due to SzO, who also showed less grey matter volume reduction. Conclusion: The emergence of psychotic spectrum symptoms in FHR was indexed by smaller cross‐sectional surface area and progressive cortical thinning. Relative preservation of surface area over time may signal different processes according to familial risk. These findings lay the foundation for future studies aimed at stratification of FHR youth.